Evaluating the Efficacy of a Structured Teaching Program on Gastritis Prevention and Management Among Pre-University Students in Shivamogga, Karnataka: A Quasi-Experimental Study - Kaul, Ashta (Journal of Research in Vocational Education, 2025)
Introduction: Gastric disorder is a common medical problem in India 5. The incidence of gastritis in India is approximately 3 in 869 people suffering from gastritis. Frequency of gastritis is decreasing in the developed world but increasing in developing countries. Gastritis is more common among the adolescents, but it can affect anyone at any age. A variety of mild to severe stomach symptoms may indicate gastritis. Gastrointestinal system is one of the systems of our body which deals with Diet - its intake, absorption, metabolism and elimination. Upper gastrointestinal inflammatory process is exceedingly common and has a wide spectrum of causes and manifestations. Hence the focus of this study was to evaluate the effectiveness of Planned teaching programme on prevention and management of gastritis among students at selected PU Colleges at Shivamogga. Methodology: A Pretest posttest with control group research design and evaluative approach was used in the study. The data was collected from 120 subjects, each 60 pre - university students in control group and 60 pre - university students in experimental group, selected through non - probability purposive sampling technique. Data was collected using structured questionnaire. Results: The overall analysis of level of knowledge of students regarding prevention and management of gastritis showed that in experimental group majority 55% of the subjects had moderate knowledge and 35% had inadequate knowledge in pre test, where as in post test 55% of subjects had adequate knowledge and 41.7% had moderate knowledge. In control group majority 58.3% of the subjects had moderate knowledge and 30% had inadequate knowledge in pre test, where as in post test 71.7% of subjects had moderate knowledge and 18.3% had adequate knowledge. The mean knowledge scores of the subjects at pre - test were 14.53 (55.88%) with standard deviation 3.529 found to be moderate knowledge regarding prevention and management of gastritis. After administration of Planned teaching programme mean knowledge scores of the subjects was 19.48 (74.92%) with standard deviation 3.327 found to be improvement in the level of knowledge among students in experimental group. In control group the pretest mean knowledge scores was found to be 14.97 (57.57%) with the standard deviation of 3.483 and the mean post test knowledge scores were 16.9 (65%) with standard deviation of 2.628 which shows the mild increase in the knowledge level of students regarding prevention and management of gastritis. Conclusion: Findings of the study show that there was a significant difference in pre test and post test level of knowledge of students in experimental group where as little increase in the knowledge scores of students in control group. From this it is concluded that the Planned teaching programme is effective in improving the level of knowledge of students. And there was a significant association between level of knowledge of students in experimental group and selected demographic variables such as age, educational status and Source of information.